Dominance hierarchy on palm resource partitioning among Neotropical frugivorous mammals - Akkawi, Paula [UNESP]; Villar, Nacho [UNESP]; Mendes, Calebe P [UNESP]; Galetti, Mauro [UNESP] (Oxford University Press (OUP), 2020)
In tropical forests, the diets of many frugivorous mammals overlap, yet how hyper-diverse assemblages of consumers exploit resources and coexist remains poorly understood. We evaluated competitive interactions among three species of terrestrial frugivorous mammals, the ungulate Tayassu pecari (white-lipped peccary), its close relative Pecari tajacu (collared peccary), and a large rodent (Dasyprocta azarae, agouti), in their exploitation strategies of palm resources of different quality. We conducted the study in a large isolated fragment at the tropical Atlantic Forest of Brazil, where these mammal species show high spatial and temporal overlap. We evaluated if body mass and foraging group size define a hierarchy in exploitation of preferentially richer palm resources. We used camera traps and two-species occupancy models to examine patterns of co-occurrence and variable interaction strength between these consumers and three species of palms. Our analyses supported the hypothesis of partial resource overlap but no competition among frugivores, and a body mass dominance hierarchical exploitation of resources. The larger frugivore (white-lipped peccary) dominated patches of the lipid-rich palm Euterpe edulis, where the smallest frugivore (agouti) was absent. Instead, the smallest frugivore concentrated its foraging in areas with the poorest palm resource, Syagrus oleracea. Collared peccaries preferred areas of high abundance of Syagrus romanzoffiana when the other two mammal species were rarely detected or absent, strongly avoided patches of E. edulis, and showed higher average detection probabilities when agoutis were present. Our study highlights the important role of behavioral plasticity in promoting coexistence and indicates that through context-dependent interactions and hierarchical partitioning of resources, consumers can avoid strong competition, even under conditions of high spatial and temporal overlap and high levels of habitat fragmentation and isolation.
Keywords: Arecaceae; armadilhas fotográficas; Brazilian Atlantic Forest; camera trap; coexistence; coexistência; competicąõ; competition; mammalian frugivores; mamíferos frugívoros; Mata Atlântica do Brasil; modelos de ocupacąõ; niche partitioning; occupancy modeling; particąõ de nicho